TI_GERICHTE 11.2011.70 vom 18. Dezember 2013 , Rapporti di vicinato: aperture e distanze di finestre dal fondo vicino - TI Tribunale d'appello (2013)
Rapporti di vicinato: aperture e distanze di finestre dal fondo vicino